2011
DOI: 10.1007/s11998-011-9343-0
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion tests of nickel coatings prepared from a Watts-type bath

Abstract: This paper deals with the preparation and characterization of thin Ni layers. The electrodeposition was carried out galvanostatically from a Watts bath at different current densities in the range from 1 to 10 A dm À2 and for deposition times between 900 and 7200 s. The structure and the morphology of the nickel coatings were investigated by SEM and XRD techniques. The microhardness of deposited layers, the electrochemical behavior and the corrosion properties of the deposits were investigated by means of Vicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…More so, composite particle has strong effect on the deposited surface structure, and the changes in deposition mechanism should be the main reason for morphology differences. The nucleation and the crystal growth could be attributed to the current density and potential, which is in agreement with previous reported result of [34]. No pores were observed on the surface of the Zn-7SnO 2 -0.3V.…”
Section: Sem/eds Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…More so, composite particle has strong effect on the deposited surface structure, and the changes in deposition mechanism should be the main reason for morphology differences. The nucleation and the crystal growth could be attributed to the current density and potential, which is in agreement with previous reported result of [34]. No pores were observed on the surface of the Zn-7SnO 2 -0.3V.…”
Section: Sem/eds Resultssupporting
confidence: 92%
“…strong plane and Zn-7SnO 2 -0.3V produced a better phase as a result of smaller crystal. It is reported that current densities often influence the produced grain size, which could determine the phase composition of such coating [19,34]. Considering the decreased sulfur in bath due to Zn 2?…”
Section: Afm Studiesmentioning
confidence: 99%
“…In line with study investigated by [10][11] microstructural modification is strongly affected by the degree of addition and the kind of particles incorporated. Deposition as a result of super saturated deposit causes agglomeration which leads to the production of harder and more resistant coatings [12].…”
Section: Introductionsupporting
confidence: 85%
“…This assertion was found true in respect to Zn-SiC-ZrO 2 content into the metal lattices resulted into solid structure thereby forming a suitable adhesion and enhancement of hardness properties. Comparison of the deposits shows that the irregularities of the particle embedded at the metal/film interface of the binary phase of SiC and ZrO 2 results to a reduction in the hardness value compare to the ternary phase which is in line with study by [7,10]. Figure 5 shows the thermo-mechanical characteristics of the deposited alloy at 200 0 C in 4 h with isothermal furnace route.…”
Section: Physical and Mechanical Behaviour Of The Fabricated Coatingssupporting
confidence: 76%
“…Effort to strengthen this atmospheric, high temperature corrosion and mechanical deformation on most fabricated components, moving vessels and equipment is thus a concern of recent [7,8]. Alloy development with thin film codeposition for the purpose of combating high temperature corrosion and improved mechanical value is now gaining ground [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%